(untitled) (MAUSAM, 2022)
Study of rainfall trend is of great importance in India where food security and consequently economy primarily dependent on rainfall. Present work is carried out to perform the detailed analysis of temporal variability in North East India rainfall. Temporal variation in monthly, seasonal and annual rainfall over northeast India (NEI) is studied using monthly data for 150 years (1857-2006). Magnitude of trend in time series data is determined by using both parametric and non-parametric test i.e linear regression and Man-Kendall test. Analysis of data suggests a significant decrease in monsoon rainfall and increase in post monsoon rainfall. Influence of global teleconnection like North Atlantic Oscillation (NAO) and Southern Oscillation (SO) on NEI rainfall is also studied to address the temporal variation. To carry out detail analysis, time series rainfall data is further divided into five normal periods of 30 year each: 1857-1886 (P1), 1887-1916 (P2), 1917-1946 (P3), 1947-1976 (P4) and 1977-2006 (P5) and trend analysis on seasonal rainfall performed for above mentioned periods. Decreasing trend for four out of the five classified periods for monsoon rainfall and significant increase in three periods obtained for post monsoon rainfall. 11 year running mean also calculated for annual as well as seasonal rainfall to see the changes in rainfall pattern.